Exploring the Potential of Generative AI in Shaping Engineering Education: Opportunities and Challenges - Yelamarthi, Kumar; Dandu, Raju; Rao, Mohan; Yanambaka, Venkata Prasanth; Mahajan, Satish (Journal of Engineering Education Transformations, 2024)
Abstract—Engineering education equips students with the necessary knowledge and skills to thrive in rapidly evolving field of engineering and computer science. However, updating the curriculum to be current with the latest advancements can be challenging for educators. The curriculum and activities (both cocurricular and extra-curricular) activities must be designed such way as to educate a global engineer with multidimensional attributes. The faculty and administrators must be willing to adapt to the fast changes in technology and learning habits of our students. In this day and age of ChatGPT, Bard, Perplexity and other generative AI tools, educators have to adapt and focus on creative ways of engaging students towards lifelong learning with strong work ethics and professional skills. This paper explores the potential of generative artificial intelligence (AI) in revolutionizing engineering education by designing and offering up-to-date content. It examines specific examples in various engineering domains and discusses the benefits of generative AI in accreditation efforts and faculty time allocation. Keywords—engineering education; generative AI; prompt engineering.